Reduction Gonioplasty: Bone Regeneration and Soft Tissue Response. Issue 6 (December 2016) - Fu, Xi; Rui, Lu; Niu, Feng; Chen, Ying; Wang, Meng; Qiao, Jia; Chen, Jing; Gui, Lai
Abstract : Background: Reduction gonioplasty is frequently used to achieve an oval-shaped face in Asia. However, the soft tissue response and bone regeneration of reduction gonioplasty which are keys to the outcome are still unclear. The aim of this study is to evaluate the effects of bone regeneration on facial width and the soft tissue response of reduction gonioplasty. Methods: We retrospectively reviewed patients who underwent reduction gonioplasty from 2009 to 2013. A high-speed rotary cutting bur without a water coolant was routinely used from the new gonial point to the inferior mandibular rim under the second premolar, whereas the elongated osteotomy line (mandibular-chin body osteotomy) was performed with a reciprocating saw. Forty-nine patients with preoperative, immediate postoperative, and 12-month postoperative frontal cephalograms were included in our study. Mandible and soft tissue profiles were measured on cephalograms. Results: Bone regeneration in high-speed rotary cutting bur ostectomy region was −0.79 ± 1.76 mm (1 cm above Go-Go), −0.75 ± 1.46 mm (Go-Go, bigonial line), and −0.77 ± 2.10 mm (1 cm below Go-Go), whereas 0.07 ± 1.79 mm (2 cm below Go-Go) in ostectomy region performed by reciprocating saw. The soft tissue response ratios were 76.72 ± 30.70% (Go-Go), 108.8 ± 54.11% (1 cm below Go-Go), and 155.9 ± 66.82% (2 cm below Go-Go). Conclusions: Bone regeneration does not lead to an increase in facial width after reduction gonioplasty with our technique, and the use of a high-speed rotary cutting bur without a water coolant decreases bone regeneration. The soft tissue response ratio is higher in the anterior mandible, and the outcome of reduction gonioplasty is a sharper lower face with a full cheek. Reduction gonioplasty is an effective and predictable lower face reshaping surgery.